1991
DOI: 10.1080/09542299.1991.11083160
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-Intestinal Absorption of Lead in Children and Adults: Overview of Biological and Biophysico-Chemical Aspects

Abstract: Intake and uptake of lead in the general population is mainly via the gastro-intestinal (GI) tract. Those biological and biophysico-chemical factors operating in the Gl tract are the main determinants of Pb bioavailability. They include sites of Pb uptake, the physiology of uptake/transport to blood, the stage of development, interactions of Pb with nutrients, and Gl biochemical transformations of ingested material. Lead uptake occurs as ion or complex, from micelles and perhaps by pinocytosis in the infant. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 91 publications
2
66
0
2
Order By: Relevance
“…Generally, the bioaccessibility of Cd in both polluted and unpolluted soils in the small intestinal phase, in which the main absorption process in human body usually takes place (Mushak, 1991;Ruby et al, 1996;Rodriguez et al, 1999), was significantly lower than in the gastric phase, possibly due to the low Cd adsorption of soil in high solution pH in part. It was reported that the adsorption of Cd in the soil increased rapidly with increasing solution pH within the range of 2-5 (Naidu et al, 1994).…”
Section: The Effect Of Ageing On Bioaccessibility In Soilsmentioning
confidence: 99%
“…Generally, the bioaccessibility of Cd in both polluted and unpolluted soils in the small intestinal phase, in which the main absorption process in human body usually takes place (Mushak, 1991;Ruby et al, 1996;Rodriguez et al, 1999), was significantly lower than in the gastric phase, possibly due to the low Cd adsorption of soil in high solution pH in part. It was reported that the adsorption of Cd in the soil increased rapidly with increasing solution pH within the range of 2-5 (Naidu et al, 1994).…”
Section: The Effect Of Ageing On Bioaccessibility In Soilsmentioning
confidence: 99%
“…However, the extent of minimization of Pb bioaccessibility in the small intestinal phase is substantially larger than that in the gastric phase. Given the fact that the absorption of lead mainly takes place in the small intestine (Mushak, 1991), the addition of P amendments has great potential for reducing its bioaccessibility of Pb from the contaminated soil effectively.…”
Section: Soluble Pb Concentration In Simulated Gastrointestinal Tractmentioning
confidence: 99%
“…Fendorf et al [28] reported that Pb bioaccessibility in the B horizon of soil from the Oak Ridge National Laboratory site declines rapidly to less than 20% within 30 days of soil incubation with a mixture of NaAsO 2 , CrCl 3 and PbCl 2 in a 0.001-M CaCl 2 matrix at pH 3 in a 1:10 (w:v) soil-to-solution ratio, whereas exchangeable Pb extracted by MgSO 4 is relatively constant with time; however, this study was conducted only in the gastric phase, without further evaluation in the small intestinal phase where the main adsorption process usually occurs [30].…”
Section: Introductionmentioning
confidence: 99%